2011
DOI: 10.1002/jcb.23081
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocytes synthesize and activate cortisol

Abstract: The bioavailability of circulating and/or endogenous hydrocortisone (cortisol) in epidermal cells is a key determinant in inflammatory disease and chronic wounds. It is not known, however, whether epidermal cells can regulate tissue cortisol and whether they are capable of producing endogenous glucocorticoids. In the present study, we show by microarray analysis that epidermal cells express mRNAs to all the major enzymes involved in the metabolic chain from cholesterol to cortisol, including cytocrome P450 cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 35 publications
2
91
1
3
Order By: Relevance
“…Although our studies were conducted in mice, the ability of human skin to synthesize cortisol de novo also remains debatable, with studies reporting both negative (Slominski et al 2002) and positive findings (Cirillo & Prime 2011, Hannen et al 2011, Vukelic et al 2011. Moreover, the quantities of cortisol generated de novo in these studies appear to be considerably lower than those reported to be generated by 11b-HSD1 in human skin (Tiganescu et al 2011(Tiganescu et al , 2013.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Although our studies were conducted in mice, the ability of human skin to synthesize cortisol de novo also remains debatable, with studies reporting both negative (Slominski et al 2002) and positive findings (Cirillo & Prime 2011, Hannen et al 2011, Vukelic et al 2011. Moreover, the quantities of cortisol generated de novo in these studies appear to be considerably lower than those reported to be generated by 11b-HSD1 in human skin (Tiganescu et al 2011(Tiganescu et al , 2013.…”
Section: Discussionmentioning
confidence: 77%
“…Expression of steroidogenic enzymes in this pathway, including cytochromes CYP11A1, CYP17A1, and CYP21A2 has been detected in human skin (Slominski et al 1996), with cortisol synthesis detected in hair follicles (Ito et al 2005), keratinocytes (Cirillo & Prime 2011, Hannen et al 2011, Vukelic et al 2011, melanocytes (Slominski et al 2005a), and fibroblasts (Slominski et al 2005b(Slominski et al , 2006. Corticosterone synthesis has also been detected in rodent skin (Slominski et al 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…11␤-HSD1 is widely expressed in human and mouse epidermis and dermis (276,699), but is highest in keratinocytes in the suprabasal area of the epidermis and dermal fibroblasts where it is a reductase (121). Keratinocyte 11␤-HSD1 increases with differentiation (699), parallelling the enzyme's pattern during differentiation of preadipocytes (510).…”
Section: Skinmentioning
confidence: 99%
“…Наряду с тканью надпочечников, синтезирующей глюкокортикоиды, все больше данных стало появ-ляться о местах вненадпочечниковой продукции кор-тизола, к ним относятся мозг, легкие, сердце, тимус, клети иммунной системы и кожа [21,22].…”
Section: синтез кортизола в коже регуляция репарацииunclassified
“…Люди с ожирением имеют высокий риск развития венозных язв, различных кожных забо-леваний (например, кандидоза, эритразмы) или более серьезных кожных инфекций (например, целлюлита, некротизирующего фасцита), гнойных осложнений после хирургических вмешательств. Однако роль ГКС в регуляции репарации ран в настоящее время доста-точно плохо изучена.Наряду с тканью надпочечников, синтезирующей глюкокортикоиды, все больше данных стало появ-ляться о местах вненадпочечниковой продукции кор-тизола, к ним относятся мозг, легкие, сердце, тимус, клети иммунной системы и кожа [21,22].Несмотря на основную функцию кожи служить барьером для защиты внутренней среды организма от агрессивных воздействий, последние исследова-ния в дерматологии были посвящены изучению спо-собности клеток эпидермиса секретировать гормоны. Способность взаимодействовать с центральной нерв-ной системой посредством локальной продукции в системный кровоток гормонов, нейропептидов, ней-ротрансмиттеров и других регуляторных факторов по-зволяет рассматривать кожу как нейроэндокринный орган [23].…”
unclassified